EFEKTIVITAS PENERAPAN TERAPI BERMAIN BOLA UNTUK MENINGKATKAN KEMAMPUAN MOTORIK KASAR PADA TUNAGRAHITA RINGAN KELAS 1 SMPLB - ANGGRAENI PUTRI HARYANI (Universitas Negeri Surabaya, 2013)
Abstract: Intellectual limitations light mental retardation in children make children become mature in response to environmental and below-average academic. Children's mental retardation in gross motor development is not comparable with increasing age. This study aims to improve gross motor skills in grades 1 SMPLB mild mental retardation. Mild mental retardation has an IQ of about 50-70. This research uses experimental research with technique of data analysis wilcoxon and descriptive. The subjects of this study were grade 1 Light Mental Retardation SMPLB in SLB AC Dharma Wanita Sidoarjo, which amounts to 5 people. Data collected with this method and observation checklist. After the test the difference before treatment and after treatment to get results and significant value of 0.041 at 0.05, it can be said that can improve gross motor skills mild mental retardation. So the hypothesis in this study states that